2019
DOI: 10.1016/j.isci.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2-Dependent GGCX and MGP Are Required for Homeostatic Calcium Regulation of Sperm Maturation

Abstract: Summary A low-calcium microenvironment is essential for spermatozoa to mature in the epididymis; however, it remains unclear how dysregulation of epididymal luminal calcium is associated with male infertility. Using a warfarin-induced vitamin K2 deficiency rat model, we found that vitamin-K-dependent γ-glutamyl carboxylase (GGCX) and matrix Gla protein (MGP) were essential in extracellular calcium signaling of the intercellular communication required for epididymal sperm maturation. We found that GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 56 publications
4
39
1
1
Order By: Relevance
“…Mgp is secreted in matrix calcifying vesicles. Another interesting possibility would be that of the involvement of Mgp in maintaining the extracellular calcium homeostasis, a recently described action of the gene shown to occur during sperm maturation 33 . In the trabecular meshwork, Mgp is carboxylated, therefore active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mgp is secreted in matrix calcifying vesicles. Another interesting possibility would be that of the involvement of Mgp in maintaining the extracellular calcium homeostasis, a recently described action of the gene shown to occur during sperm maturation 33 . In the trabecular meshwork, Mgp is carboxylated, therefore active.…”
Section: Discussionmentioning
confidence: 99%
“…In the trabecular meshwork, Mgp is carboxylated, therefore active. In the sperm, it was shown that uncarboxylated, inactive MGP which loses its ability to bind calcium, contributes to high Ca concentrations in the epididymal lumen 33 . It would be interesting to determine whether the absence of Mgp in the outflow pathway cells could also disturb the Ca levels on the ECM which could in turn affect extracellular calcium entry and modulate trabecular meshwork function 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct distribution or oscillation of calcium levels and the expression of its regulatory proteins during spermatogenesis suggest that calcium signaling may play an essential role in spermatogenesis, in particular in the regulation of the growth and apoptosis of spermatogonia and spermatocytes [7,8]. Calcium signals also participate in the process of epididymal sperm maturation [9]. Studies have shown that some calcium channels maintain calcium homeostasis and regulate calcium signals, in turn affecting spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin K is important for many physiological processes as the cofactor of the gamma-glutamyl carboxylase (GGCX) enzyme [2,3]. This enzyme is involved in the activation of many proteins, called vitamin K-dependent proteins (VKDPs), by catalyzing their γ-glutamyl carboxylation.…”
Section: Introductionmentioning
confidence: 99%